2019
DOI: 10.1002/acm2.12567
|View full text |Cite
|
Sign up to set email alerts
|

Distributive quality assurance and delivery of stereotactic ablative radiotherapy treatments amongst beam matched linear accelerators: A feasibility study

Abstract: Purpose Beam matching occurs on all linacs to some degree and when two are more are matched to each other, patients are able to be transferred between machines. Quality assurance of plans can also be performed “distributively” on any of the matched linacs. The degree to which machines are matched and how this translates to like delivery of plans has been the focus of a number of studies. This concept has not yet been explored for stereotactic techniques which require a higher degree of accuracy. This study pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…For the three linacs, the maximum difference in the mean GPR and the median GPR was 0.72% and 0.80%, respectively. In terms of the GPR, this result indicates that the three linacs are well beam matched 29,30 . In the control chart, linac1 showed much noise in the PSQA data; linac2 initially showed significant noise before stabilizing; and linac3 initially showed some noise, stabilized, and finally became noisy again.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For the three linacs, the maximum difference in the mean GPR and the median GPR was 0.72% and 0.80%, respectively. In terms of the GPR, this result indicates that the three linacs are well beam matched 29,30 . In the control chart, linac1 showed much noise in the PSQA data; linac2 initially showed significant noise before stabilizing; and linac3 initially showed some noise, stabilized, and finally became noisy again.…”
Section: Discussionmentioning
confidence: 80%
“…In terms of the GPR, this result indicates that the three linacs are well beam matched. 29,30 In the control chart, linac1 showed much noise in the PSQA data; linac2 initially showed significant noise before stabilizing; and linac3 initially showed some noise, stabilized, and finally became noisy again. Critically, the LCL of linac2 obtained from the three non-normal-based methods was about 2% lower than that of linac1 and 3% lower than that of linac3.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, parameters such as coincidence of kV‐MV isocenter, and of radiation–mechanical isocenter, were ensured to be ≤1 mm as per TG‐142 tolerances for linacs used for SRS, 26 and average deviation from the radiation isocenter to a ball‐bearing center for all acquired projections was ≤0.75 mm for Winston‐Lutz tests. These criteria, which are also stricter than those suggested by Hrbacek et al, 16 Sarkar et al, 27 and Xu et al 28 were shown to be sufficient for distributive QA and delivery of cases more complex than single‐target SRS, such as stereotactic body radiotherapy (SBRT) to vertebral lesions 24 …”
Section: Methodsmentioning
confidence: 96%
“…The four linacs (referred to as FS1, ST3, TC1, and TC2) were Elekta Versa HD® (Elekta, Crawley, UK), equipped with Agility™ MLC of leaf width 5 mm. Their 6 MV flattening filter free (FFF) beams were matched using criteria recommended by Rijken et al, 24 which add to those outlined by the vendor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation